Value and Values : Economics and Justice in an Age of Global Interdependence - Hershock, Peter D.; Ames, Roger T., 1947- (Book collections on Project MUSE., 2015)
This work brings together leading thinkers from around the world to deliberate on how best to correlate worth (value) with what is worthwhile (values), pairing human prosperity with personal, environmental, and spiritual flourishing in a world of differing visions of what constitutes a moral life.